2018
DOI: 10.1038/s41377-018-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal camouflage based on the phase-changing material GST

Abstract: Camouflage technology has attracted growing interest for many thermal applications. Previous experimental demonstrations of thermal camouflage technology have not adequately explored the ability to continuously camouflage objects either at varying background temperatures or for wide observation angles. In this study, a thermal camouflage device incorporating the phase-changing material Ge2Sb2Te5 (GST) is experimentally demonstrated. It has been shown that near-perfect thermal camouflage can be continuously ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
191
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 307 publications
(191 citation statements)
references
References 66 publications
0
191
0
Order By: Relevance
“…d) Infrared images of the pattern of a GST‐based emitter. Reproduced with permission . Copyright 2018, Nature Publishing Group.…”
Section: Phase Change Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…d) Infrared images of the pattern of a GST‐based emitter. Reproduced with permission . Copyright 2018, Nature Publishing Group.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…Exploiting the material property of GST at wavelength below 660 nm, i.e., where Re(ε cr‐GST ) < 0 and Re(ε am‐GST ) > 0, Gholipour et al demonstrated a GST nanograting metasurface that exhibits switchable reflection/transmission behavior accompanied with remarkable color changes (Figure c), showing the potential of the proposed metasurface for active solid‐state displays . The nonvolatile phase transition properties of GST films can be applied to realize controllable mid‐infrared thermal emission . It should be noted that contrary to the emissivity tuning of the GST‐hybrid, the modulation addressed in these studies arises from the intrinsic emission change of the GST structures.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…Phase-change memory (PCM) materials work by switching between their amorphous and crystalline phases under an appropriate electrical or laser pulse [1][2][3][4][5] . At the same time, the great contrasts in resistance and refractive index/reflectivity between the two phases ensure the applications of PCM materials in both non-volatile electrical and optical memory [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…So far, strategies for breaking the 50% absorption limit in the visible and infrared region are mainly based on metal‐dielectric schemes. These strategies include metal–insulator–metal plasmonic absorbers, dielectric‐on‐metal absorbers, film stacks‐based Fabry‐Perot cavity absorbers, etc. However, for these designs with the aid of metals, a significant portion of absorption takes place in metals, where heat instead of photocarriers is generated.…”
Section: Introductionmentioning
confidence: 99%